Physical Quality of The House as a Risk Factor for ARI Disease in Toddlers in Working Area of The Gentungan Health Center - Nur Haidah; Surya Annisa; Mulyadi; Juherah; Sulasmi (Poltekkes Kemenkes Surabaya, 2024)
Acute Respiratory Infection (ARI) cases became the number one disease in Gowa Regency in 2020, with a total of 17,394 cases and a percentage of 8.52% of the top ten diseases. Several factors, including unhealthy home environment factors, can cause ARI. Data on healthy homes in the Gentungan Health Centre area is 3,328 out of 6,163 houses examined from 7,704 houses. This study aimed to determine the relationship between the physical quality of the house and the incidence of ARI in the Gentungan Health Centre working area, Gowa Regency. This type of research is analytical and observational with a case-control approach. There were 134 samples, 67 case samples, and 67 control samples. Samples in this study used systematic random sampling. The results showed there was a significant relationship between temperature (p=0.000), humidity (p=0.003), and ventilation (p=0.005) with the incidence of ARI in toddlers, and there was no significant relationship between lighting (p = 0.791) and the incidence of ARI disease in toddlers. It is expected that the Gentungan Health Centre can counsel the community about the importance of maintaining the physical quality of the house and the dangers of ARI. Then, the community is expected to control the risk factors for ARI by improving the physical quality of the house and for further researchers to conduct research related to the relationship between the physical quality of the house and ARI disease the incidence of ARI in toddlers.